Optimizing Inventory Management Through the Inventory Information System at PT Lintas Cakrawala - Anjas Ramadhani; Martua Hami Siregar; Encep Fahmi Imaduddin; Supriatin; Herryansyah (J-INTECH ( Journal of Information and Technology), 2026)
The issue of stock management Optimization at PT. Lintas Cakrawala has so far been handled manually; the company lacks a proper inventory information system, which often leads to inaccurate results and increases the likelihood of recording errors, resulting in financial losses for the company. The objective of this research is to analyse system requirements and design a web-based inventory information system as a solution to optimise stock management at PT. Lintas Cakrawala. Furthermore, this research aims to address the issue of data discrepancies between manual records and the physical condition of goods, which can hinder decision-making. The method used in this study is the Waterfall software development model, which comprises the stages of requirements analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observation and a review of documentation relating to the existing system. The performance test results showed that the new system had an average response time of 1.2 seconds for real-time stock tracking. It also cut down the time needed to create inventory reports from about 120 minutes when done manually to just 1.8 minutes with the automated system. These results show a big boost in how well the operations are running and back up how good the new inventory information system is working. This system is expected to minimise human error, prevent stockouts and overstocking, and improve operational efficiency within the warehouse division of PT. Lintas Cakrawala